2011
DOI: 10.1016/j.autneu.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia augments sympatho-excitatory response to ATP but not to l-glutamate in the RVLM of rats

Abstract: The development of sympathetic overactivity and hypertension in rats submitted to chronic intermittent hypoxia (CIH) involve alterations in the central mechanisms controlling respiratory and autonomic functions. Herein, we assessed whether CIH alters glutamatergic and/or purinergic signaling in the ventrolateral medulla (VLM), a region that encompasses the pre-sympathetic neurons and respiratory neurons of the ventral respiratory column. Groups of juvenile rats were exposed for 10 days to CIH (6% O(2) for 40s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Expression is also observed in downstream sympathetic regulatory cell groups, including neurons in the hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (8,27). Importantly, full expression of hypertension in our 7-day CIH model critically depends on activator protein-1 transcriptional regulation of MnPO neurons by FosB/⌬FosB (8).These and other observations (7,9,40,41,46,70) indicate that exaggerated SNA and the neurogenic component of CIHinduced hypertension are complex and might not arise solely from the sensitization of arterial chemoreceptors. In the present study, we sought to determine the early contribution of forebrain/hypothalamic neural mechanisms in hypertension induced by 7 days of CIH.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Expression is also observed in downstream sympathetic regulatory cell groups, including neurons in the hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (8,27). Importantly, full expression of hypertension in our 7-day CIH model critically depends on activator protein-1 transcriptional regulation of MnPO neurons by FosB/⌬FosB (8).These and other observations (7,9,40,41,46,70) indicate that exaggerated SNA and the neurogenic component of CIHinduced hypertension are complex and might not arise solely from the sensitization of arterial chemoreceptors. In the present study, we sought to determine the early contribution of forebrain/hypothalamic neural mechanisms in hypertension induced by 7 days of CIH.…”
mentioning
confidence: 65%
“…These and other observations (7,9,40,41,46,70) indicate that exaggerated SNA and the neurogenic component of CIHinduced hypertension are complex and might not arise solely from the sensitization of arterial chemoreceptors. In the present study, we sought to determine the early contribution of forebrain/hypothalamic neural mechanisms in hypertension induced by 7 days of CIH.…”
mentioning
confidence: 92%
“…In vitro, loose-patch recordings from RTN neurons show that P2 receptor blockers decreased responsiveness to both 10% and 15% CO 2 also by 30%. In the slice, the contribution of purinergic signalling to RTN chemoreception did not increase with temperature (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • C) and was retained in low extracellular Ca 2+ medium. Conversely, the gap junction blockers carbenoxolone and cobalt decreased neuronal CO 2 /H + sensitivity by an amount similar to P2 receptor antagonists.…”
Section: Key Pointsmentioning
confidence: 99%
“…57 Previous evidence showed that C1 cells are key determinants of the sympa thoexcitatory response to peripheral chemoreceptor activa tion. 15 In addition, an animal model of OSA showed that chronic intermittent hypoxia increased sympathoexcitatory responsiveness to RVLM injections of ATP, 28 suggesting that purinergic signaling in this region contributes to OSA induced activation of sympathetic activity and hypertension. Here, we show that purinergic signaling contributes to the peripheral chemoreflex at the level of the RVLM by a P2Y1 receptor-dependent mechanism.…”
Section: Physiological Significancementioning
confidence: 99%
See 1 more Smart Citation